Relationship Life Cycle of Organizational and Leadership Styles (Case Study of Kermanshah City Administration, Government Agencies) - Rahmanseresht, Hossein; Yavari, Eghbal (International Review of Management and Marketing, 2017)
This study investigated the relationship between different stages of the life cycle of organizational and leadership styles in the offices of government agencies Kermanshah province. This descriptive study with a quantitative approach and appropriate information gathered from a sample of 402 people. The data gathering tool was a standard questionnaire. Therefore, the model of Miller and Friesen (1984) was used to identify the stages of the life cycle and has had 20 questions, each of the stages of birth, growth, maturity, decline and revival is measured with four items and the leadership model Rensys Likert (1961) was used to identify leadership practices. The questionnaire has 27 questions, imperious manner with 7 items, charitable way with 6 items, consultative approach with 6 items and collaborative manner is measured by 8 items. The population of the entire staff of managers and administrative staff, including 27 Department of Kermanshah city with a population of 8526 people. Bartlett test was used to assess reliability. Content validity was used for validity; the questionnaire was sent to a number of professors in the field of research and after the reforms were attempted to distribute it. The results of the tests "Bartlett" calculated for the concept of leadership style equal to 0.702 and for the life cycle of the 0.891 was decided to confirm the adequacy of sampling (more than 0.50). For analyze the software "SPSS" and Amos were used. The results show that organizational life and its dimensions ranging between cycles of birth, growth, maturity, decline and revival and leadership styles include authoritarian, benevolent, consultation and participation, there is a significant correlation between positive effects. Keywords: Life Cycle of Organizational, Leadership Style, Administration and Government Agencies JEL Classifications: C32; O13; O47